1999
DOI: 10.1016/s0167-4889(98)00172-4
|View full text |Cite
|
Sign up to set email alerts
|

Glucose metabolism in Neurospora is altered by heat shock and by disruption of HSP30

Abstract: We compared the metabolism of [1-13C]glucose by wild type cells of Neurospora crassa at normal growth temperature and at heat shock temperatures, using nuclear magnetic resonance analysis of cell extracts. High temperature led to increased incorporation of 13C into trehalose, relative to all other metabolites, and there was undetectable synthesis of glycerol, which was a prominent metabolite of glucose at normal temperature (30 degrees C). Heat shock strongly reduced formation of tricarboxylic acid cycle inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Previously published studies have shown that metabolites that can be readily used as carbon sources, such as glutamate and trehalose, are found in dormant spores of N. crassa (61). A role for trehalose as a thermal protectant has been established for N. crassa (56). This previous work also demonstrated that although trehalose is a large component of the metabolite pool in conidia, the relative levels of trehalose are similar in conidia and hyphae of wild-type strains.…”
Section: Vol 10 2011 Metabolic Profiling In Neurospora 825mentioning
confidence: 77%
“…Previously published studies have shown that metabolites that can be readily used as carbon sources, such as glutamate and trehalose, are found in dormant spores of N. crassa (61). A role for trehalose as a thermal protectant has been established for N. crassa (56). This previous work also demonstrated that although trehalose is a large component of the metabolite pool in conidia, the relative levels of trehalose are similar in conidia and hyphae of wild-type strains.…”
Section: Vol 10 2011 Metabolic Profiling In Neurospora 825mentioning
confidence: 77%
“…In this way it depletes the cells of ATP, as well as blocking glycolysis and other steps in glucose metabolism (30). Glycolysis and heat shock-induced glycolytic enzymes appear to be especially important for energy generation at high temperature (56,57). Although phosphorylated 2-DG has been reported to act as a high-glucose signal, e.g., in activating Akt kinase (20,61), the chief effect of 2-DG in our assays likely stems from its inhibition of glucose metabolism, since another glucose analog, Lsorbose, that is not phosphorylated (66) also leads to cell death, albeit less dramatically and at higher concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In response to high temperature, carbohydrate metabolism changes from a focus on oxidative respiration to an increase in glycolysis and fermentation [23]. However, addition of an inhibitor of glycolysis, such as 2-DG, would be expected to shift the balance from intense glycolysis to increased oxidative respiration.…”
Section: Resultsmentioning
confidence: 99%
“…This response is also characterized by increased reliance on glycolysis for energy generation [3] at the expense of mitochondrial oxidative respiration. We have asked whether cell recovery from heat shock could be compromised if glycolysis simultaneously was blocked by glucose starvation, induced by a glucose metabolism inhibitor, 2-deoxyglucose (2-DG) [4].…”
Section: Introductionmentioning
confidence: 99%